Pengaturan Pelayanan Kesehatan Paliatif Bagi Masyarakat Miskin dalam Jaminan Kesehatan Nasional - Susanti, Yulia; Syofyan, Syofirman (Faculty of Law, Andalas University, 2025)
Health services are the rights of every individual that the state must guarantee through sustainable policies and systems. Law Number 17 of 2023 concerning Health has included palliative services as part of health services. Still, its implementation in the National Health Insurance (JKN) has not been explicitly regulated in other regulations, such as Law Number 40 of 2004 concerning the National Social Security System and Presidential Regulation Number 59 of 2024 concerning Health Insurance. This creates legal uncertainty, especially in ensuring poor access to palliative services, resulting in significant social, economic, and infrastructure barriers. This study aims to analyze the arrangement of palliative health services in the JKN system, identify the obstacles faced by people experiencing poverty in accessing these services, and determine what efforts can be made. The research was conducted with a normative juridical approach, using secondary data from primary, secondary, and tertiary legal materials. The analysis was conducted qualitatively to understand the legal problem and its impact on implementing palliative services. The results show that palliative care has not been explicitly recognized as part of the guaranteed benefits in JKN, leading to uncertainty in financing, a lack of service standards, and discrimination against the poor in access. To overcome this, it is necessary to strengthen regulations, prepare national guidelines for palliative services, increase the capacity of health workers, and allocate special budgets. This effort is expected to ensure equitable access to palliative services for all levels of society, especially low-income people.